Triglyceride/Glucose Index (TyG Index) as a marker of glucose status conversion among reproductive-aged women in Jakarta, Indonesia: The Bogor cohort study (2011–2016). Issue 6 (November 2021) - Liberty, Iche A.; Kodim, Nasrin; Sartika, Ratu A.D.; Trihandini, Indang; Tjekyan, R.M. Suryadi; Zulkarnain; Pane, Masdalina; Pratisthita, Livy B.; Tahapary, Dicky L.; Soewondo, Pradana
Abstract: Background and aims: Reproductive-aged women are prone to type 2 diabetes mellitus. This study aims to evaluate the optimal cut off point of Triglyceride/Glucose Index for predicting glucose status conversion among women of reproductive age. Methods: This study involved normoglycemic and prediabetes women aged 20–49 years from the Bogor Non-Communicable Diseases Cohort Study (West Java, Indonesia) conducted from 2011 to 2016. Statistical analysis was performed using Receiver Operating Characteristics curve analysis with STATA version 15. Results: Among prediabetes subjects (n = 371), the cut-off point of TyG index for regression from prediabetes to normoglycemic subjects was <4.51 [sensitivity, specificity, AUC (95%CI) 83.9%, 80.1%, 0.913 (0.875–0.943), respectively] and the cut-off point for progression from prediabetes to diabetes was >4.54 [80.0%, 73.1%, 0.858 (0.807–0.900)]. Among normoglycemic subjects (n = 1300), the cut-off point of TyG index for progression to prediabetes and diabetes were >4.44 [80.1%, 71.1%, 0.834 (0.812–0.854)] and >4.47 [80.6%, 80.8%, 0.909 (0.890–0.926)] respectively. Conclusion: Based on sample of subjects evaluated between 2011 and 2016, TyG index appears to be a promising marker for glucose status conversion among reproductive-aged women in Jakarta, Indonesia. Highlights: Conversion of glucose homeostasis in women at reproductive age Insulin resistance as a risk of type 2 diabetes melitus in women at reproductive age Assessment of insulin resistance in limited healthcare facilities using triglyceride/glucose index Progression and regression of prediabetes state in women at reproductive age